2009
DOI: 10.1002/jcp.21689
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs controlling human ovarian cell steroidogenesis via a genome‐scale screen

Abstract: The aim of our studies was to identify miRNAs affecting the release of the major ovarian steroid hormones progestagen, androgen and estrogen by human ovarian cells. The effect of transfection of cultured primary ovarian granulosa cells with 80 different gene constructs encoding human pre-miRNAs on release of progesterone, testosterone and estradiol was evaluated by enzyme immunoassay. In addition, effect of two selected antisense constructs blocking corresponding miRNA on progesterone release was tested. Effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(136 citation statements)
references
References 29 publications
5
128
1
2
Order By: Relevance
“…Whether, physiologically, miR-224, miR-383 and miR-378 are each involved in regulation of aromatase during different stages of follicle development has not been determined. In addition, large-scale functional testing in human granulosa cells revealed effects of multiple miRNAs on the production of progesterone, testosterone and oestradiol, as well as in the expression of the markers of proliferation and apoptosis, PCNA and BAX, although no attempt was made to investigate the mechanisms involved in these responses (Sirotkin et al 2009(Sirotkin et al , 2010.…”
Section: Involvement Of Mirnas During Follicular Growth and Steroidogmentioning
confidence: 99%
“…Whether, physiologically, miR-224, miR-383 and miR-378 are each involved in regulation of aromatase during different stages of follicle development has not been determined. In addition, large-scale functional testing in human granulosa cells revealed effects of multiple miRNAs on the production of progesterone, testosterone and oestradiol, as well as in the expression of the markers of proliferation and apoptosis, PCNA and BAX, although no attempt was made to investigate the mechanisms involved in these responses (Sirotkin et al 2009(Sirotkin et al , 2010.…”
Section: Involvement Of Mirnas During Follicular Growth and Steroidogmentioning
confidence: 99%
“…A recent study showed that level of miR-378 in the follicular wall was correlated with estradiol, the estradiol: progesterone ratio and CYP19A1 (Donadeu et al, 2016). MiR-34a and miR-320 inhibit estradiol release from human granulosa cells and murine ovaries, respectively (Sirotkin et al, 2009;Yao et al, 2014). However, miR-320 could stimulate testosterone and progesterone in murine ovaries.…”
Section: Mirnas In Steroidogenesis and Their Hormonal Regulationmentioning
confidence: 98%
“…The effect of miRNAs on the release of major ovarian steroid hormones was determined by transfecting human primary granulosa cells with 80 different human pre-miRNAs constructs, and the release of progesterone was inhibited by 36 miRNAs. Whereas, 10 miRNAs promoted progesterone release (Sirotkin et al, 2009). MiR-378 decreases ovarian estradiol production by targeting aromatase.…”
Section: Mirnas In Steroidogenesis and Their Hormonal Regulationmentioning
confidence: 99%
“…Unfortunately, these studies neither explored the targets of these miRNAs, which may be regulated to modulate cell apoptosis/ proliferation, nor did they examine what factors may modulate the expression of these miRNAs. Sirotkin et al (2009) used an identical approach to identify miRNAs that regulate ovarian cell steroidogenesis. Thirty-six miRNAs that inhibited progesterone release and ten miRNAs that enhanced progesterone release were identified ( Table 2).…”
Section: Ovarymentioning
confidence: 99%